Maternal intake of folate and folic acid during pregnancy and markers of male fecundity: A population‐based cohort study. (26th December 2022) - Gaml‐Sørensen, Anne; Brix, Nis; Høyer, Birgit Bjerre; Tøttenborg, Sandra Søgaard; Hougaard, Karin Sørig; Bonde, Jens Peter Ellekilde; Clemmensen, Pernille Jul; Ernst, Andreas; Arendt, Linn Håkonsen; Olsen, Sjurdur Frodi; Granström, Charlotta; Henriksen, Tine Brink; et al.
Abstract: Background: Poor male fecundity is of concern, and a prenatal origin has been proposed. Folate, a methyl donor involved in DNA methylation, is essential for normal fetal development by regulating gene expression during different periods of fetal development. Thus, prenatal exposure to low maternal folate intake might have a programing function of the developing reproductive organs. Objectives: To examine the association between maternal intake of folate from diet and folic acid from supplements during pregnancy and markers of fecundity in young men. Materials and methods: We conducted a follow‐up study using a Danish mother–son cohort of 787 young men born 1998–2000. Percentage differences in semen characteristics, testes volume, and reproductive hormone levels were analyzed according to total folate calculated as dietary folate equivalents from diet and supplements in midpregnancy, using multivariable negative binomial regression models. Total folate was analyzed in quintiles, continuous per standard deviation decrease (SD: 318 μg/day) and as restricted cubic splines. Results: Low maternal intake of total folate was associated with lower total sperm count (−5% (95% confidence intervals [CI]: −11%; 2%)), a lower proportion of non‐progressive and immotile spermatozoa (−5% [95% CI: −8%; −3%]), and lower testes volume (−4% [95% CI: −6%; −2%]) per SD decrease in total folate intake. Spline plots supported these findings. Discussion: The finding of a lower proportion of non‐progressive and immotile spermatozoa, and hence a higher proportion of motile spermatozoa, in men of mothers with a lower intake of total folate in midpregnancy was surprising and may be a chance finding. Conclusion: Lower maternal intake of total folate in midpregnancy was associated with lower sperm count and lower testes volume, however, also with a lower proportion of non‐progressive and immotile spermatozoa in adult men. Whether this actually affects the ability to obtain a pregnancy warrants further investigation.